Youth of the tula region in the labor market: perspectives of employment - Natalia Alexandrovna Kondratenko; Svetlana Nicolaevna Shashkova (Вестник Майкопского государственного технологического университета, 2023)
The article analyzes the employment prospects of Tula youth in the regional labor market. It has been noted that the proximity of the metropolitan area is a factor that affects the local labor market, as modern young people are focused on fast career growth and high wages that the regional labor market is not able to supply. The analysis of the results of the sociological research conducted by the laboratory of social and political research of Tula State University in 2018 revealed common “non-educational” motives for higher education and lack of interest in chosen profession among students. Main reasons for a high level frictional unemployment among youth have been described briefly, including, on the one hand, the inability of young people to build communication with a potential employer, lack of self-presentation skills and an ability to search for suitable vacancies in various sources of information independently, lack of desire to work intensively and finish their work on the new workplace in accordance with production needs, and on the other hand, the unwillingness of employers to hire unexperienced staff, to train young people in accordance with the specifics of their enterprise. Measures to solve the identified problems have been proposed, which include information, career guidance and educational resources.